Validity of Prothrombin-induced Vitamin K antagonist versus Alpha-Fetoprotein (Tumor Markers) in Diagnosis of Hepatocellular Carcinoma, Using Computed Tomography scan as Gold Standard: Validity of prothrombin-induced Vitamin K antagonist versus Alpha-Fetoprotein in Hepatocellular Carcinoma Diagnosis - Latif, Amer; Saeed, Riffat; Banghash, Tariq Ali; Shahzad, Muhammad Khawar; Ahmed, Hassam; Naveed, Muhammad Asif; Amer, Usama (Pakistan Journal of Health Sciences, 2024)
Biomarkers like alpha-fetoprotein and prothrombin-induced Vitamin K deficiency/ antagonist are used in the early diagnosis and staging of hepatocellular carcinoma and are useful for better outcomes in the treatment and overall survival of the patient. Objective: To compare the diagnostic accuracy of alpha-fetoprotein and prothrombin-induced Vitamin K antagonist in the diagnosis of hepatocellular carcinoma using a computed tomography scan as a gold standard. Methods: A cross-sectional study was conducted in the Liver Transplant Unit of Shaikh Zayed Postgraduate Medical Complex, Lahore from July 2023 to January 2024. A total of 94 patients older than 12 years old with cirrhosis and CT scan suggestive of hepatocellular carcinoma were selected. Blood was collected to test for AFP and PIVKA-II. The samples were sent to the labs after labeling them properly and the results were collected and entered in the data sheet. Patients were advised to have a multiphase contrast-enhanced CT scan. Patients were followed up in the clinic after 7 days. Results: The diagnostic accuracy of AFP was 78% with a 74.7% sensitivity, 100% specificity, 100% positive predictive value, and 41.67% negative predictive value. The diagnostic accuracy of PIKVA-II was found to be 87.76% with 89% sensitivity, 80% specificity, 96.1% PPV, and 57.14% NPV. Conclusions: On comparing the tumor markers AFP with PIVKA-II against the gold standard multiphase CT scan it was found that PIVKA-II has better diagnostic accuracy than AFP.